Temperature dependence of the dielectric strength of zinc sulfide films; Russian Physics Journal; Vol. 39, iss. 6 - Zhigal'skii A. A.; Ikonnikova L. F. Liubov Fedorovna; Minakova T. S.; Mukhachev V. A.; Troyan P. E. (1996, 1996)
Title screen